Sonographic and CT imaging features of intestinal perforation from a pill and packing: A case report. Issue 16 (April 2018) - Gou, Ze-hui; Peng, Yulan; Yang, Kun
Abstract: Rationale: Sharp foreign bodies such as toothpicks or chicken bones can lead to intestinal perforation. Small intestinal perforation secondary to foreign body ingestion is usually manifested as an acute abdomen without a history of trauma. Here we describe the diagnosis and treatment of a case of small bowel perforation caused by an ingested pill and its outer packing. Patient concerns: An 84 years old male patient complained of right lower abdominal pain for 4 days and the pain was becoming progressively worse. Diagnoses: The patient, who has Alzheimer's disease, mistakenly took the pill (oxiracetam) without removing the outer packaging. This resulted in perforation of the small intestine. Interventions: During the ultrasound examination, the scanning physician discovered that the abnormal sonographic findings present could not be explained by the leading diagnosis of perforation of the small intestine at the time. This led the physician to suspect small bowel perforation secondary to a foreign body. The subsequent computerized tomography (CT) examination further confirmed the ultrasound findings. Outcomes: Emergency laparotomy was performed and the foreign body was removed. After the surgical procedure, the patient resumed anti-inflammatory treatment (Cefoxitin sodium 2000mg tid) and rehydration therapy (Sodium Chloride Solution 100mL tid). Lessons: Because ingestion of foreign bodies of this type is relatively rare, when patients cannot provide an accurate history, diagnosis can be quite difficult. In this paper, the imaging features associated with intestinal perforation secondary to foreign body ingestion on ultrasound and CT are described. This series of events demonstrate how imaging findings can guide and alter a clinician's decision-making.